2017
DOI: 10.1007/s12011-017-1097-9
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Protects against Lead-induced Apoptosis via Endoplasmic Reticulum Stress in Chicken Kidneys

Abstract: Lead (Pb) is a toxic heavy metal and can harm organisms by inducing apoptosis. Selenium (Se), an essential trace element for humans and animals, can alleviate heavy metal toxicity. The aim of our study is to investigate alleviative effect of Se on Pb-induced apoptosis via endoplasmic reticulum (ER) stress in chicken kidneys. One hundred and eighty male chickens were randomly divided into four groups at 7 days of age and were fed with commercial diet (containing 0.49 mg/kg Se) and drinking water, NaSeO-added co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Furthermore, Se appears to be mediated through its antiapoptosis effect to protect against tissue or cell damage. Previous studies have demonstrated that Se significantly ameliorated apoptosis and the changes of apoptosis-related genes or proteins via decreasing the expression of the ER stressrelated genes or proteins GRP78, GRP94, ATF4, ATF6, and IRE in cadmium or lead-treated chicken kidney and ovary (Liu et al 2015b;Wan et al 2018;Wang et al 2018). Also, our results showed that Se clearly inhibited ER stress and apoptosis induced by ZEN exposure.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, Se appears to be mediated through its antiapoptosis effect to protect against tissue or cell damage. Previous studies have demonstrated that Se significantly ameliorated apoptosis and the changes of apoptosis-related genes or proteins via decreasing the expression of the ER stressrelated genes or proteins GRP78, GRP94, ATF4, ATF6, and IRE in cadmium or lead-treated chicken kidney and ovary (Liu et al 2015b;Wan et al 2018;Wang et al 2018). Also, our results showed that Se clearly inhibited ER stress and apoptosis induced by ZEN exposure.…”
Section: Discussionsupporting
confidence: 73%
“…Also, in ZEN-caused reproductive system damage, high levels of Se improved antioxidant ability, and inhibited reproductive cell apoptosis (Long et al 2016). In chicken, Se could ameliorate cadmium or lead-induced cytotoxicity, oxidative stress, ER stress, and apoptosis in the splenic lymphocytes, kidney, testis, ovary, and liver (Chen et al 2012;Liu et al 2015b;Wan et al 2018;Wang et al 2018). Moreover, a Se-deficient diet can cause the occurrence of oxidative stress and hepatocyte apoptosis (Yao et al 2015), but dietary supplementation with Se reduced germ cells apoptosis in the testis during spermatogenesis in chicken (Song et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…20 Some researchers reported that selenium could ameliorate Pb and Cd poisoning by decreasing GRP78 and GRP94. 55,67,68 Our results indicated that selenium could alleviate the increased mRNA expressions of GRP78 and GRP94 caused by AFB 1 , and no significant differences of these values were observed between the +Se group and the control group. This study showed that selenium may Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Antioxidative and stress-relieving effects of selenium compounds have been reported in several cellular stress conditions, including but not limited to heat shock response, oxidative stress, and ER stress [51,52,53]. It has been clarified that the antioxidative function of selenium, when supplied at rational levels corresponding to physiological optima, is through incorporating into selenoproteins with oxidoreductase functions [30].…”
Section: Discussionmentioning
confidence: 99%